Dangerous mediations pop music in a Philippine prison video - Mangaoang, Áine (New approaches to sound, music, and media, 2019)
In 2007, 1500 prisoners in Cebu Provincial Detention and Rehabilitation Centre (CPDRC) became bona fide Internet celebrities following their YouTube interpretation of Michael Jackson's groundbreaking music video "Thriller." Emboldened by the public's overwhelmingly positive response to this unusual music video, CPDRC officials instigated a mandatory daily dance and pop music performance schedule, uploading new videos onto YouTube that received millions of views. Officials then introduced a monthly, live, public performance held within the prison yard, creating a unique tourism industry surrounding the prison walls, and in 2010 a national "prison dance rehabilitation" policy was introduced by the Filipino government.0Connecting scholarship on popular music with emerging literature on YouTube's audiovisuality, musicologist Aine Mangaoang combines first-hand experience of visiting the prison and textual analysis with a critical and holistic approach. As such, this is the first book to examine the disquieting trend of prisoners serving as musical performers and digital entertainers to a global audienc